PENGARUH KEPEMILIKAN SAHAM MANAJERIAL DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Sektor Pertambangan yang terdaftar di Bursa Efek Indonesia Periode 2011-2013) - Faitullah, Anang (Jurnal Manajemen, 2019)
The problem formulation of this research were (1) whether The Ownership of Managerial Stock and Corporate Social Responsibility Disclosure affects simultaneously to The Firm Value at mining sector companies registered in Indonesia Stock Exchange for periode of 2011-2013?, (2) whether The Ownership of Managerial Stock and Corporate Social Responsibility Disclosure affects partially to The Firm Value at mining sector companies registered in Indonesia Stock Exchange for periode of 2011-2013?. The objective of this research were determine : (1) whether there is any effect between The Ownership of Managerial Stock and Corporate Social Responsibility Disclosure affects simultaneously to The Firm Value at mining sector companies registered in Indonesia Stock Exchange for periode of 2011-2013, (2) whether there is any effect between The Ownership of Managerial Stock and Corporate Social Responsibility Disclosure affects partially to The Firm Value at mining sector companies registered in Indonesia Stock Exchange for period of 2011-2013. The population of this research was the mining sector companies registered in Indonesia Stock Exchange. The sample selection used was purposive sampling method. The analysis tool used was multiple linear regression which is managed by using SPSS ver. 16.0. Based on the result showed that as simultaneously and partially The Ownership Of Managerial Stock and Corporate Social Responsibility Disclosure did not have any significant effect to The Firm Value.